Writers’ awareness of metadiscourse features in Malaysian business news - Hooy, Chee Mei; Tan, Helen; Lee, Geok Imm; Victor Danarajan, Sharon Sharmini (Universiti Malaysia Sarawak, 2022)
Metadiscourse is an important linguistic resource in business news because it guides readers throughout the text. Business news is vital to keep people abreast of how the economy affects job opportunities, how high or low interest rates may go, and whether layoffs are imminent in local industries. However, it is the news that people read the least because it is not engaging to them. The study aims to investigate The Star Onlineand Focus Malaysiabusiness news writers’ awareness on the use of metadiscourse features. Metadiscourse Awareness Test was given to 10 business news writers from The Star Onlineand Focus Malaysiarespectively. The findings showed that sequencers had the lowest mean score (M=2.334) for textual metadiscourse, while certainty markers hadthe lowest mean score (M=2.667) for interpersonal metadiscourse. Although The Star Onlineand Focus Malaysia writers exhibited the lowest mean score in identifying sequencers and certainty markers, they still demonstrated a high awareness in identifying all the categories of textual and interpersonal metadiscourse. The findings revealed the importance of metadiscourse features for the business news writers to fully utilise them in the news industry.